Chemical Composition and Functional properties of Caesalpina bonduc and Monodara myristica seed flours - A.E, Adeleke; A, Sangoremi; S.A, Adegbite (International Journal of Environment, Agriculture and Biotechnology, 2019)
The chemical composition, nature minerals, anti-nutrients, functional and physicochemical properties of Caesalpina bonduc and Monodara myristica seed flours were determined. The results for proximate compositions in the samples were for Caesalpinia bonduc flour were moisture (7.89%), Ash (2.96%), Crude protein (18.26%), Crude fibre (12.54%), fat content (23.59%) and Carbohydrate (34.76%) while for Monodora myristica flour were: moisture (5.05%), Ash content (2.81%), crude fibre (4.69%), crude protein (24.62%), fat content (7.01%) and carbohydrate (55.82%). The mineral contents in (mg/l) for Caesalpinia bonduc and Monodara myristica seed flours were: K(36.68), (101.87), Ca(40.98), (59.43), Na (475.65), (463.57), Mg (13.20), (14.80), Zn (61.80), (66.20), P (18.5), (23.86), Ni (14.70), (13.40), Fe (12.80), (28.3), Cu (0.06) and (0.08) respectively. These results showed that the seeds samples contained some valuable minerals that are useful in bone formation as well as physiological and metabolic activities. The results of the functional properties for Caesalpina bonduc and Monodora myrictca seeds flours were: gelation capacities (51.40%), (53.80%), water absorption capacities (113.00), (121.50), emulsion capacities(56.25%), (56.00%), swelling capacities(7.10), (6.80) and oil Absorption capacities (137.50%), (115.50) and foaming capacities were (5.05) and (5.00) respectively. The anti-nutritents contents for Caesapina bonduc and Monodora myristica reported in this study were: Phytate (0.406%), (0.37%) Saponin (0.184%), (0.172%), Oxalates (0.068%), (0.056%), Tannins (0.083%) and (0.074%) respectively.This result suggested that the seed flours have low anti-nutritional content and may be useful in food formulations like doughes and baked products. It also confirmed that the seed samples may be good substitutes for wheat flour and Soy flour as extender in binder formulation.